A Genome-wide Association Study of Periodontitis in a Japanese Population. (April 2015) - Shimizu, S.; Momozawa, Y.; Takahashi, A.; Nagasawa, T.; Ashikawa, K.; Terada, Y.; Izumi, Y.; Kobayashi, H.; Tsuji, M.; Kubo, M.; Furuichi, Y.
Periodontitis is a multifactorial disease in which bacterial, lifestyle, and genetic factors are involved. Although previous genetic association studies identified several susceptibility genes for periodontitis in European populations, there is little information for Asian populations. Here, we conducted a genome-wide association study and a replication study consisting of 2, 760 Japanese periodontitis patients and 15, 158 Japanese controls. Although single-nucleotide polymorphisms that surpassed a stringent genome-wide significance threshold ( P < 5 × 10 −8 ) were not identified, we found 2 suggestive loci for periodontitis: KCNQ5 on chromosome 6q13 (rs9446777, P = 4.83 × 10 −6, odds ratio = 0.82) and GPR141-NME8 at chromosome 7p14.1 (rs2392510, P = 4.17 × 10 −6, odds ratio = 0.87). A stratified analysis indicated that the GPR141-NME8 locus had a strong genetic effect on the susceptibility to generalized periodontitis in Japanese individuals with a history of smoking. In conclusion, this study identified 2 suggestive loci for periodontitis in a Japanese population. This study should contribute to a further understanding of genetic factors for enhanced susceptibility to periodontitis.